Pemberdayaan Kelompok Rentan Pasca Banjir Bandang Melalui Edukasi Kesehatan dan Pengelolaan Lingkungan di Nagari Pandai Sikek - Yessy Markolinda Markolinda; Mery Ramadani; Trisfa Augia; Randy Novirsa; Frima Elda; Kamal Kasra; Bunga Putri Aurora; Melati Putria Efendi; Fathiya Zarine Deca; Mardhiah Cahyani BP (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
This activity aimed to improve the quality of life and public health post-disaster through an integrated approach in health and disaster management. The service was conducted from September 21 to November 13, 2024, using methods of included socialization, simulations, and education using pre-test and post-test approaches to measure intervention effectiveness. Activities were carried out in the form of disaster mitigation counseling for elementary school students involving 200 students, maggot-based waste management training with more 30 participants, healthy lifestyle education for the elderly through the GERMAS program, and nutrition education for parents to prevent stunting with more than 20 participants. The results showed an increase in community understanding of disaster mitigation, with the average pre-test score rising from 58,4 to 82,7 in the post-test. The community demonstrated a better understanding of the importance of waste management to prevent environmental pollution, awareness of early hypertension detection, and fulfillment of balanced nutrition to prevent stunting. Active participation in simulations, Q&A sessions, and discussions serves as indicators of the activity success. It can be concluded that this community service program successfully enhanced the knowledge and awareness of the Pandai Sikek community regarding health and disaster preparedness. The sustainability of this program requires support through collaboration with local governments, educational institutions, and community groups to expand its positive impact. It is recommended to actively involve younger generations and strengthen implementation monitoring to optimize and sustain the program's outcomes.